Alveolar echinococcosis in solid organ transplant recipients: a case series from two national cohorts - Marquis Bastian; Demonmerot Florent; Richou Carine; Thiéfin Gérard; Millon Laurence; Wallon Martine; Vuitton Dominique Angèle; Grall-Jezequel Anne; Grenouillet Frédéric; Epaulard Olivier; Gervais Philippe; Manuel Oriol; et al. (Parasite, 2023)
Alveolar echinococcosis (AE) is a severe parasitic infection caused by the ingestion of Echinococcus multilocularis eggs. While higher incidence and faster evolution have been reported in immunosuppressed patients, no studies have been performed specifically on AE in transplant patients. We searched for all de novo AE cases diagnosed between January 2008 and August 2018 in solid organ transplant (SOT) recipients included in the Swiss Transplant Cohort Study and the FrancEchino Registry. Eight cases were identified (kidney = 5, lung = 2, heart = 1, liver = 0), half of which were asymptomatic at diagnosis. AE diagnosis was difficult due to the low sensitivity (60%) of the standard screening serology (Em2+) and the frequently atypical radiological presentations. Conversely, Echinococcus Western blot retained good diagnostic performances and was positive in all eight cases. Five patients underwent surgery, but complete resection could only be achieved in one case. Moreover, two patients died of peri-operative complications. Albendazole was initiated in seven patients and was well tolerated. Overall, AE regressed in one, stabilized in three, and progressed in one case, and had an overall mortality of 37.5% (3/8 patients). Our data suggest that AE has a higher mortality and a faster clinical course in SOT recipients; they also suggest that the parasitic disease might be due to the reactivation of latent microscopic liver lesions through immune suppression. Western blot serology should be preferred in this population. Finally, surgery should be considered with caution, because of its low success rate and high mortality, and conservative treatment with albendazole is well tolerated.